(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Cassia angustifolia Vahl (family Caesalpiniaceae), commonly known as ‘‘sanaai,’’ is a fast growing and spreading Indian shrub of which seeds, pods and leaves are extensively used for pharmaceutical applications. The seeds have been found to be an alternative source of commercial gums and are used as an anthelmintic, digestive, and to treat piles, skin diseases, and abdominal troubles. The current investigation found that a water-soluble galactomannan consisting of D-galactose and D-mannose in the molar ratio 3 4 has been isolated from the seeds of Cassia angustifolia. Hydrolysis of the methylated polysaccharide resulted in three methylated sugars (i) 2, 3-di-O-methyl-D-mannose, (ii) 2, 3, 4-tri-O-methyl-D-galactose, and (iii) 2, 3, 4, 6-tetra O-methyl-D-galactose in the molar ratio 2 1 2 Periodate oxidation of the polysaccharide indicated 61 end group while methylation gave 60 . Reduction of the periodate oxidized polysaccharide and subsequent hydrolysis revealed the presence of (1→ 4) and (1→6) glycosidic bonds. Thus, the main chain of the galactomannan was found to consist of (1→4)-linked mannoypyranosyl units having 3-glycosidic bonds while (1→6)-linked α-glycosidically bonded galactopyranosyl units form the branching points.